Improvement of antioxidant capacity, aroma quality, and antifungal ability of cherry by phenyllactic acid treatment during low temperature storage - Zhang, Chaoqi; Wang, Yunfan; Wang, Mengxin; Kong, Yanhui; Li, Xiulian; Song, Danliangmin; Zeng, Xiangquan; Yang, Yanqing; Fan, Xinguang; Gong, Hansheng (Frontiers in Plant Science, 2024)
IntroductionSweet cherries (Prunus avium L.) are highly valued for their taste and nutrients but are prone to decay due to their delicate skin and high respiration rate. Traditional chemical preservatives have drawbacks like residues and resistance, prompting the search for natural alternatives. Phenylactic acid (PLA) has shown promise due to its antibacterial and antioxidant properties, making it a potential natural preservative to extend cherry shelf life.Methods'Stella' sweet cherries were treated with varying concentrations of PLA (0, 2, 4, 8, 16 mmol·L-1) and stored at 4°C. Key quality indicators, including firmness, total acidity, total soluble solids, weight loss, decay index, and antioxidant activity, were assessed over time. Additionally, HPLC, GC-MS, GC-IMS, colony counts, in vivo inhibition analyses were conducted to evaluate phenolic content, aroma compounds and antifungal ability.Results and DiscussionPLA at 8 mmol·L-1 effectively maintained cherry quality by reducing weight loss and decay of cherries, delaying the decline of firmness, while enhancing antioxidant capacity, flavor stability, and antifungal ability. Higher concentrations (16 mmol·L-1) provided stronger antimicrobial effects but caused slight surface wrinkling. Thus, 8 mmol·L-1 was optimal, balancing preservation and appearance, making it a promising natural preservative for extending cherry shelf life.